THE “SEDEKAH BUMI” LOCAL WISDOM APPROACH TO HELPING ELEMENTARY SCHOOL STUDENTS UNDERSTAND CLIMATE CHANGE ISSUES - Alfian Firdaus S; Ari Metalin Ika Puspita; Ganes Gunansyah (LP2M IAI Al-Khairat Pamekasan, 2026)
Climate change has become an urgent global issue, while elementary school students’ understanding and actions regarding this issue remain limited. Learning in schools tends to be theoretical and has not yet integrated contextual local values. This study aims to develop a learning design based on the local wisdom of Sedekah Bumi to enhance students’ understanding of climate change and to foster environmental care character. The study employed a descriptive qualitative approach using a design research model, involving 20 fifth-grade students at SD Negeri Gedongboyountung. Data were collected through observations, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The results indicate that integrating Sedekah Bumi values improves students’ conceptual understanding of climate change and promotes attitudes of mutual cooperation, responsibility, and environmental awareness. The learning process becomes more contextual, meaningful, and enjoyable. The findings support the integration of local wisdom into environmental education curricula to create sustainable learning that is relevant to the Indonesian cultural context.